PREFERENSI SMARTPHONE SEBAGAI ALAT PERJALANAN WISATA DI BALI - I Made Kusuma Negara; Putu Agus Wikanatha Sagita (Department of Tour and Travel Studies, Faculty of Tourism, Udayana University, 2021)
Utilization of tourism information and communication technology has an impact on increasing tourist satisfaction. One of them is the use of smartphones as a travel tool such as booking accommodation, selecting destinations, searching for tourist locations, distance to tourist sites, weather at tourist sites, uploading travel memories, and other travel needs. This study aims to describe the social, economic, demographic variables of tourists in using smartphones as a travel tool in Bali. The basic needs of tourists such as hotels and restaurants are the main needs of tourists in browsing through smartphones. In addition, the conditions at the destination are also a relatively important need for tourists to know through the use of smartphones. Women as domestic tourists dominate the use of smartphones in traveling, most of whom are women who live in metropolitan areas. Meanwhile, for foreign tourists, it looks proportionally distributed based on the country of origin of the tourists. Those who are well-educated dominate the use of smartphones in traveling. The distribution of young and productive ages can also be seen clearly in using smartphones as a travel tool. Even in the case of foreign tourists, the elderly also contributes to the use of smartphones as a travel tool.